Heparin-mediated selective release of hepatocyte growth factor in humans - Salbach, Peter Bernhard (Blackwell Science Inc, 2000)
AIMS: The aim of this investigation was to compare the effects of standard (S) with low molecular weight (LMW) heparin on circulating levels of heparin-binding growth factors (HBGF), known to have angiogenic properties in humans. METHODS: In two consecutive trials 18 healthy male voluteers were studied on three separate occasions, following a placebo-controlled crossover design. Subjects were randomised to receive either S-heparin or LMW heparin or placebo. Heparins were administered either by intravenous (i.v.) or subcutaneous (s.c.) injection and saline placebo by i.v. injection. Serum concentrations of hepatocyte growth factor (HGF), vascular endothelial cell growth factor (VEGF) and basic fibroblast growth factor (bFGF) were measured before and up to 24 h after injection. RESULTS: Administration of i.v. S-or LMW-heparin (50 IU kg(−1)) resulted in rapid, highly significant (47 fold for S, 30.9 fold for LMW) increases in HGF serum values, reaching maxima of 10.51 ± 1.65 ng ml(−1) (S) and 8.28 ± 1.04 ng ml(−1) (LMW), respectively, 10 min after drug application. S.c. injection of S-heparin or LMW heparin resulted in 4.1 and 5.4 fold increases in HGF serum values, respectively. Both agents showed no effects on circulating VEGF or bFGF levels, independent of the route of administration. CONCLUSIONS: Circulating HGF levels were selectively increased in response to pharmacological doses of two, widely used heparin preparations. This may, in part, explain some of the biological effects of heparin separate from its anticoagulant properties. By this mechanism, the systemic administration of heparin may facilitate collateral vessel formation in various clinical settings of tissue ischaemia.